Invariant Natural Killer T Cells in Immune Regulation of Blood Cancers: Harnessing Their Potential in Immunotherapies - Lam, Pui Yeng; Nissen, Michael D.; Mattarollo, Stephen R. (Frontiers in Immunology, 2017)
Invariant natural killer T (iNKT) cells are a unique innate T lymphocyte population that possess cytolytic properties and profound immunoregulatory activities. iNKT cells play an important role in the immune surveillance of blood cancers. They predominantly recognize glycolipid antigens presented on CD1d, but their activation and cytolytic activities are not confined to CD1d expressing cells. iNKT cell stimulation and subsequent production of immunomodulatory cytokines serve to enhance the overall anti-tumor immune response. Crucially, the activation of iNKT cells in cancer often precedes the activation and priming of other immune effector cells, such as NK cells and T cells, thereby influencing the generation and outcome of the anti-tumor immune response. Blood cancers can evade or dampen iNKT cell responses by downregulating expression of recognition receptors or by actively suppressing or diverting iNKT cell functions. This review will discuss literature on iNKT cell activity and associated dysregulation in blood cancers as well as highlight some of the strategies designed to harness and enhance iNKT cell functions against blood cancers.